Prevention of noise-induced hearing loss by calpain inhibitor MDL-28170 is associated with upregulation of PI3K/Akt survival signaling pathway - Lai, Ruosha; Fang, Qiaojun; Wu, Fan; Pan, Song; Haque, Khujista; Sha, Su-Hua (Frontiers in Cellular Neuroscience, 2023)
Noise-induced calcium overload in sensory hair cells has been well documented as an early step in the pathogenesis of noise-induced hearing loss (NIHL). Alterations in cellular calcium homeostasis mediate a series of cellular events, including activation of calcium-dependent protein kinases and phosphatases. Using cell-membrane- and blood-brain-barrier permeable calpain-1 (µ-calpain) and calpain-2 (m-calpain) inhibitor MDL-28170, we tested the involvement of calpains, a family of calcium-dependent cysteine proteases, and the potential of MDL-28170 in preventing NIHL. CBA/J mice at the age of 12 weeks were exposed to broadband noise with a frequency spectrum from 2–20 kHz for 2 h at 101 dB sound pressure level to induce permanent hearing loss as measured by auditory brainstem response and distortion product otoacoustic emissions. Morphological damage was assessed by quantification of remaining sensory hair cells and inner hair cell synapses two weeks after the exposure. MDL-28170 treatment by intraperitoneal injection significantly attenuated noise-induced functional deficits and cochlear pathologies. MDL-28170 treatment also prevented noise-induced cleavage of alpha-fodrin, a substrate for calpain-1. Furthermore, MDL-28170 treatment prevented reduction of PI3K/Akt signaling after exposure to noise and upregulated p85α and p-Akt (s473) in outer hair cells. These results indicate that noise-induced calpain activation negatively regulates PI3K/Akt downstream signaling, and that prevention of NIHL by treatment with MDL-28170 is associated with upregulation of PI3K/Akt survival signaling pathways.